Fold-Related Faults Track Progressive Fold Development from Layer-Parallel Shortening to Subsequent Orthogonal Extension within an Appalachian Buckle Fold System: Bear Valley Mine, Shamokin, PA, USA - Arlo Brandon Weil; Mary Beth Gray; Kylie G. Cush; Mattathias D. Needle; Juliet G. Crider (Lithosphere)
Outstanding three-dimensional exposures of adjacent folds in an abandoned coal mine within the Appalachian Valley-and-Ridge tectonic province permit a detailed analysis of macroscopic strain accommodation by minor faulting in the lead up to and during buckle folding. A kinematic analysis of more than 900 outcrop-scale faults coupled with clearly established relative age relationships allows delineation of distinctive fault sets and their roles in accommodating strain within a quartz-dominated sandstone and an overlying silty shale. Conjugate contractional faults are interpreted as evidence of layer-parallel shortening (LPS) prior to and during fold initiation, based on geometric relationships to primary bedding. A clearly overprinting population of younger conjugate faults accommodate layer-parallel extension (LPE) that is both parallel and perpendicular to the fold axes; they are interpreted to have developed during fold limb rotation and fold tightening. Curving and overprinting slip lineations on some strike-slip faults track the transition from LPS to LPE during fold growth. Although the fault-related extensional linear strain magnitudes are relatively small, LPE faults are present in all fold dip domains, in two contrasting lithologies, and on adjacent open and tight folds, highlighting the importance of minor faulting and LPE strains in the formation of contractional buckle folds in the shallow crust. Our findings do not strictly conform with those predicted by classical conceptual models of buckle folds, such as orthogonal flexure or flexural slip. The work further suggests that bed-parallel extension, both axis-parallel and perpendicular, is an underappreciated component of three-dimensional, buckle folding–induced strain and that models for minor fault sets that accommodate three-dimensional strain during fold formation are currently incomplete.